Neglecting the low risk in sports betting - Boda, Márton Attila (Studia Mundi – Economica, 2017)
The study shows the most popular sports betting and gambling strategies. With using these strategies the aim is to let the player reach stable profit in the long run. However these strategies cannot be implemented in a profitable way in the long run, still many players believe that they work. In the study I examine the martingale, d’Alembert, Paroli and Labouchère strategies with Monte Carlo simulation. In case of different strategies I present what attracts players to use these betting strategies and where are the traps and pitfalls of these strategies. Thereafter I examine the success-rate of soccer betting in case of different strength of opponents. Finally I present the two most important pitfalls of the betting strategies: the bad estimation of risks and the limited resources. The most important reason why players believe in these strategies is the availability heuristic.